Prevalence and its associated factors of medical error reporting among healthcare professionals in Ethiopia: Systematic review and meta-analysis - Yeshiambaw Eshetie; Tigabu Munye Aytenew; Yirgalem Abere; Bekalu Mekonen Belay; Tekalign Amera; Mengistu Ewunetu; Gebrie Kassaw Yirga; Yohannes Tesfahun; Melese Kebede; Demewoz Kefale (PLoS ONE, 2025)
Introduction Medical error refers to a mistake made by a healthcare professional that poses a significant threat to patient safety worldwide. Reporting these errors is crucial for reducing healthcare-related mistakes. Despite several studies on medical error reporting and its associated factors among health professionals in Ethiopia, the national prevalence and contributing factors are not well established. Methods. We conducted a systematic review and meta-analysis of cross-sectional studies assessing the prevalence of medical error reporting and its associated factors among healthcare professionals in Ethiopia. An extensive literature search was performed from April 10 to June 10, 2024, using databases such as Google Scholar, Web of Science, and PubMed, along with a manual search. The pooled prevalence was calculated using a random-effects model. Results Out of 1233 studies retrieved from databases, only 24 studies involving a total of 6,745 healthcare professionals were included in the analysis. The overall pooled prevalence of medical error reporting was 42.66% (95% CI: 33.19, 52.13; I2 = 98.79%, p < 0.01). Factors significantly associated with medical error reporting included being trained (AOR = 3.25, 95% CI: 1.79, 4.70), fear of administrative sanctions (AOR = 0.40, 95% CI: 0.04, 0.76), lack of feedback (AOR = 0.86, 95% CI: 0.16, 1.55; p < 0.02), increased work experience (AOR = 2.90, 95%CI: 1.25, 4.54), female professionals (AOR = 2.22, 95% CI: 0.10, 4.34), and higher education status (AOR = 3.20, 95%CI: 1.10, 5.30). Conclusion Medical error reporting among healthcare professionals in Ethiopia is relatively low, primarily due to inadequate training, fear of consequences, and lack of feedback. Targeted interventions such as training programs and the creation of a non-punitive error reporting environment are needed to improve reporting practices.